TEACHERSâ PERCEPTION ON STUDENTSâ LEXICOGRAMMATICAL ERRORS IN THEIR E-MAIL WRITING IN SECOND SEMESTER ROOM DIVISION CLASS IN BALI TOURISM INSTITUTE BASED ON TEACHERSâ GENDER AND LEVEL OF EXPERTISE - Susanti, Luh Eka; Padmadewi, Ni Nyoman; Budasi, I Gede (Jurnal Pendidikan Bahasa Inggris, 2013)
Abstract This study aimed at 1) analyzing the forms of the studentsâ lexicogrammatical errors, 2) analyzing the teachersâ correction on the studentsâ lexicogrammatical errors, and 3) describing the teachers âperception on the studentsâ lexicogrammatical errors whether it is a normal thing as a part of learning or as an obstacle which hinder the studentsâ progress. The subjects were two English teachers and second semester Room Division students. This study was designed in the form of descriptive qualitative research and the instruments being used were human instrument, questionnaire, and interview. The findings show that 1) there were 19 categories of errors that occurred in the studentsâ writings, 2) both of the subjects used direct correction, but there were some similarities and differences in the forms and the functions, and 3) the teachersâ perceptions were classified into 4 major points, namely perception on writing and its problems, perception on the nature of lexicogrammatical errors, perception on the value of errors, and perception on the sources of errors. Â Â Keywords: lexicogrammatical errors, teachersâ correction, teachersâ perception